Monkfish Peptides Mitigate High Fat Diet-Induced Hepatic Steatosis in Mice - Jiena Ye; Xiaoxiao Tian; Qiongfen Wang; Jiawen Zheng; Yanzhuo Yang; Baogui Xu; Shuai Zhang; Falei Yuan; Zuisu Yang (Marine Drugs, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a hepatic metabolic syndrome usually accompanied by fatty degeneration and functional impairment. The aim of the study was to determine whether monkfish peptides (LPs) could ameliorate high-fat diet (HFD)-induced NAFLD and its underlying mechanisms. NAFLD was induced in mice by giving them an HFD for eight weeks, after which LPs were administered in various dosages. In comparison to the HFD control group: body weight in the LP-treated groups decreased by 23–28%; triacylglycerol levels in the blood decreased by 16–35%; and low-density lipoproteins levels in the blood decreased by 23–51%. Additionally, we found that LPs elevated the activity of hepatic antioxidant enzymes and reduced the inflammatory reactions within fatty liver tissue. Investigating the effect on metabolic pathways, we found that in LP-treated mice: the levels of phospho-AMP-activated protein kinase (p-AMPK), and phospho-acetyl CoA carboxylase (p-ACC) in the AMP-activated protein kinase (AMPK) pathway were up-regulated and the levels of downstream sterol regulatory element-binding transcription factor 1 (SREBP-1) were down-regulated; lipid oxidation increased and free fatty acid (FFA) accumulation decreased (revealed by the increased carnitine palmitoyltransferase-1 (CPT-1) and the decreased fatty acid synthase (FASN) expression, respectively); the nuclear factor erythroid-2-related factor 2 (Nrf2) antioxidant pathway was activated; and the levels of heme oxygenase-1 (HO-1) and nicotinamide quinone oxidoreductase 1 (NQO1) were increased. Overall, all these findings demonstrated that LPs can improve the antioxidant capacity of liver to alleviate NAFLD progression mainly through modulating the AMPK and Nrf2 pathways, and thus it could be considered as an effective candidate in the treatment of human NAFLD.